Azerbaijan Bibliography, Modern International Databases on Natural Sciences: Formation, Structure and Use in the Azerbaijan’s Library and Bibliography Practice - Hajiyeva, Khayala (Nazarbayev University Library, 2020)
ciences, the investigation of their methodological structure and usage issues of these databases in Azerbaijan and in the world. Methodology. The research examines two areas of bibliography on natural sciences: 1. The National bibliography of Azerbaijan, and 2. Modern library databases, and their benefits to structure methodology, and data modeling. The history of formation of libraries and information resources on natural sciences in Azerbaijan, and the improvement stages they have taken during this period have been highlighted. Findings. Results show that asides from the advantages of databases and the success of library databases in library practice in the world, there were also difficulties and problems of creating the local bibliographic database for the natural sciences. Originality. Examples and experiences of local libraries are discussed in the paper and compared with the world’s leading library and bibliography practices. It covers scientific research on the principles of creating global electronic bibliographic databases on natural sciences, the principles of structural formation and the use of information resources in this area. The article reports the development of modern electronic bibliographic databases and their perspectives in Azerbaijan and abroad.
Keywords: library databases; natural sciences; global databases on natural sciences; data modeling; annotation database